PELAKSANAAN FUNGSI PEMERINTAHAN DESA GUMANTI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU TAHUN 2020-2021 - Rahmadani, Nur Aines; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The implementation of the empowerment function of the Gumanti Village government on the facilitator indicator, and the implementation of the development function of the Gumanti Village government on the innovator indicator and the implementation of the village government function is the responsibility for the implementation of development, empowerment and services. Village government is the organization of village government affairs and community interests. In the field, several problems were found, such as damaged roads in hamlet III, weak village community development and long service times. This research was conducted to see how the implementation of the Gumanti Village government function was carried out and to find out the factors that became obstacles and supporting factors for the implementation of the Gumanti Village government function. The research approach used is a qualitative approach. This type of research is descriptive. The location of this research is in Gumanti Village, Peranap District, Indragiri Hulu Regency. The types and sources of data for this research are divided into primary data and secondary data with data collection techniques through interviews and secondary data in the form of village archives and village data. The results of this study are the implementation of the government function of Gumanti Village, Peranap District, Indragiri Hulu Regency is not optimal, there are still several indicators that still need to be improved, in the implementation of the government service function of Gumanti Village there are indicators of efficiency, effectiveness, and competence. Furthermore, the implementation of modernizers. Meanwhile, indicators that have been running well are indicators of equality, motivators and stabilizers. Factors that hinder the implementation of the Gumanti Village government function are lack of community participation, inactive village websites, electricity that always goes out and lack of human resources. While the supporting factors are sufficient APBDes funds, good service orientation and discipline. Keywords: Service Function, Development, Empowerment.